Physico-Chemical Characteristics of Sediment Quality in Srirangam sub watershed of Tiruchirappalli District of Tamilnadu - Nirmala Devi, M.; T.Rajaram, Dr. (International Journal of Engineering and Technology, 2018)
A study of River Cauvery of Srirangam sub-watershed was conducted to evaluate the physico-chemical Parameters of the sediments for pre-monsoon, monsoon and post monsoon period of 2013-14, in order to check the impacts of agricultural runoff, effluents coming from watershed area on the river sediments at seven different sites in River Cauvery of Srirangam stretch. The results revealed that the average physico â€“ chemical parameter values are more in pre-monsoon period and EC,Cl, Total Organic Matter, Phosphate, Total Nitrogen, Sodium and Potassium values are comparatively less in post-monsoon period. The concentration of trace metals chromium and zinc are more in both the seasons. This is the result of discharge of domestic, municipal and agricultural discharge in the stretch.Â